PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MENGGUNAKAN MEDIA WORDWALL UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS VI PADA PELAJARAN BAHASA INDONESIA - Yulianti; Suci Asrinda; Andi Quraisy; Rafida (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Indonesia subject ini school has an important role in helping students develop systematic, logical, critical, creative and consistent thinking skills. However, the results of observation show that the level of student activity in learningdi Indonesian in class VI A is still low, which has the potential to hinder the achievement of learning objectives. This research aims to increase students' activeness in learning Indonesian through the application of the Problem Based Learning (PBL) learning model and the use of Wordwall learning media. The method used was classroom action research with research subjects 34 class VI students at UPT SD Inpres Bontoala 1. Data was collected through observation and documentation sheets, and research was carried out in two cycles, each consisting of planning, action, observation and reflection stages. The research results show that the application of the PBL learning model with Wordwall media significantly increases student activity. In the pre-cycle, the level of student activity only reached 57.14%, increasing to 67.64% in cycle I, and reaching 80% in cycle II. Based on these results, it can be concluded that the Problem Based Learning learning model using Wordwall media is effective in increasing students' activeness in learning Indonesian at UPT SD Inpres Bontoala 1.